2010
DOI: 10.1111/j.1365-2885.2009.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic properties of toceranib phosphate (Palladia™, SU11654), a novel tyrosine kinase inhibitor, in laboratory dogs and dogs with mast cell tumors

Abstract: Toceranib phosphate (Palladia, SU11654), an oral tyrosine-kinase inhibitor, is under investigation for the treatment of mast cell tumors in dogs. The pharmacokinetics of toceranib phosphate has been characterized in dogs. Means of the following pharmacokinetic parameters were estimated following a 1.0 mg/kg i.v. dose to laboratory beagles: plasma clearance of 1.45 L/kg/h, volume of distribution of 29.7 L/kg, and terminal half-life of 17.7 h. Following single oral doses of 3.25 mg/kg administered to laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 6 publications
2
33
1
1
Order By: Relevance
“…This lack of apparent cross-resistance to the conventional cytotoxic agents VBL and CCNU suggests that these drugs may remain active in patients with TOC-refractory disease. In dogs, the range of achievable concentrations for TOC in vivo has been reported between 30 nM (Cmin) and 200 nM (Cmax) [19,20]. In the current study, growth inhibition assays were carried out to 1 uM, nearly 5-fold the reported Cmax for TOC.…”
Section: Discussionmentioning
confidence: 92%
“…This lack of apparent cross-resistance to the conventional cytotoxic agents VBL and CCNU suggests that these drugs may remain active in patients with TOC-refractory disease. In dogs, the range of achievable concentrations for TOC in vivo has been reported between 30 nM (Cmin) and 200 nM (Cmax) [19,20]. In the current study, growth inhibition assays were carried out to 1 uM, nearly 5-fold the reported Cmax for TOC.…”
Section: Discussionmentioning
confidence: 92%
“…Physical examination, routine bloodwork (CBC, biochemistry profile) and blood sampling for assessment of toceranib and VEGF plasma concentrations was performed pretreatment and on days 0, 7, 14 and 30 of treatment. On days 0, 7, and 14, blood was collected at 6 and 8 hours post drug administration to coincide with the predicted toceranib Cmax based on previous studies that had established the time of maximum drug concentration (Tmax) to be 5.3-9.3 hours [7,8]. On day 30, blood sampling was performed at 0, 1, 2, 6, 8, and 12 hours post drug administration to confirm either 6 or 8 hours as the true Cmax.…”
Section: Methodsmentioning
confidence: 99%
“…Toceranib was quantitated in plasma samples using the method previously described [7,8]. Briefly, 50 μL aliquots of plasma were fortified with an internal standard (IS), a deuterated toceranib analog.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations